2003
DOI: 10.1021/jp030431e
|View full text |Cite
|
Sign up to set email alerts
|

Inclusion Complexes Oriented in Thermotropic Liquid-Crystalline Solvents Studied with Carbon-13 NMR

Abstract: The inclusion complex of cryptophane-A and chloroform dissolved in two non-chiral liquid crystalline environments was investigated via 13 C NMR. Stable solutions of oriented complexes were prepared using aromatic (ZLI 1132) and aliphatic (ZLI 1695) thermotropic nematic liquid crystals as solvents; ordering of the complexes was manifested by the 1 H-13 C dipolar splitting of the 13 C resonance of labeled chloroform. In both solutions, the dipolar splitting for the bound ligands was substantially larger than … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
22
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 15 publications
(27 citation statements)
references
References 18 publications
5
22
0
Order By: Relevance
“…Utilizing previously obtained information concerning the relative orientation of chloroform in cryptophane cages [32], the results are consistent with overall alignment of both complexes such that the cage principal axis lies roughly perpendicular to the LC director-in agreement with previous results and predictions [27]. These results demonstrate the potential for utilizing NMR measurement of anisotropic interactions restored by LC matrices for probing the structure, dynamics, and ordering behavior of host-guest inclusion complexes.…”
Section: Introductionsupporting
confidence: 88%
See 4 more Smart Citations
“…Utilizing previously obtained information concerning the relative orientation of chloroform in cryptophane cages [32], the results are consistent with overall alignment of both complexes such that the cage principal axis lies roughly perpendicular to the LC director-in agreement with previous results and predictions [27]. These results demonstrate the potential for utilizing NMR measurement of anisotropic interactions restored by LC matrices for probing the structure, dynamics, and ordering behavior of host-guest inclusion complexes.…”
Section: Introductionsupporting
confidence: 88%
“…Our motivation has been to investigate the use of LC alignment to perform novel NMR studies of structural and dynamical aspects of host-guest interactions. In our previous experiments involving aligned complexes of chloroform and cryptophane-A [27], we observed enhanced ordering for trapped ligands in aligned complexes as manifested by the observed 1 H-13 C intramolecular dipolar couplings and performed variable-temperature NMR studies of the guest 13 C signals to probe the molecular alignment in an aliphatic LC (ZLI 1695). Additionally, observations of linewidth reductions for the trapped ligand resonance upon high-power 1 H heteronuclear decoupling indirectly suggested that intermolecular dipolar couplings between host and guest had been partially restored as well.…”
Section: Introductionmentioning
confidence: 96%
See 3 more Smart Citations